Pengaruh Pemahaman Wajib Pajak, Sosialisasi Perpajakan, Sanksi Perpajakan dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Sugiarto, Renata Briliant Fernanda; Syaiful, Syaiful (Journal of Culture Accounting and Auditing, 2022)
This study aims to determine the effect of taxpayer understanding, tax socialization, tax sanctions and taxpayer awareness on individual taxpayer compliance. This study used 99 respondents. This research approach uses a quantitative approach, the source of data in this study is primary data and the type of data is subject data. Using multiple linear regression analysis method. Hypothesis testing is done by using the t test and F test to determine the effect of the independent variable on the dependent. The results of this study indicate that the Taxpayer Understanding variable has a positive and significant effect on Individual Taxpayer Compliance, Tax Socialization has a positive and significant impact on Individual Taxpayer Compliance, Tax Sanctions have a positive and significant impact on Individual Taxpayer Compliance, and Taxpayer Awareness has a positive effect. and significant to Individual Taxpayer Compliance.